Echocardiographic assessment of CRT candidates. Does it work equally well in intermediate QRS duration?. (25th November 2020) - Duchenne, J; Cvijic, M; Aalen, J.M; Larsen, C.K; Galli, E; Penicka, M; Fehske, W; Hopp, E; Stankovic, I; Smiseth, O.A; Donal, E; Voigt, J.U
Abstract: Background: The presence of mechanical dyssynchrony – such as apical rocking (ApRock) and septal flash (SF) – on echocardiography is associated with favourable outcome after cardiac resynchronization therapy (CRT). Myocardial scar on the other hand, has a considerable negative impact on CRT response. There is growing evidence that a visual echocardiographic assessment of mechanical dyssynchrony by ApRock, SF and scar predicts CRT response. Little is known however if this works equally well in patients with intermediate QRS duration (120–150ms), where guideline recommendation for CRT is weaker. Methods: A total of 400 unselected patients referred for CRT, who fulfil the contemporary guidelines, were enrolled in this multicentre study. Echocardiographic images were visually assessed before CRT implantation, focussing on the presence of ApRock, SF and location and extent of scar segments in the left ventricle (LV), resulting in a CRT response prediction (i.e. Reader Interpretation). Readers were blinded to all patient information other than ischaemic aetiology of heart failure. CRT response was defined as ≥15% reduction in LV end-systolic volume on echocardiography, on average 15 months after device implantation. Results: Overall, 321 (80%) patients had a left bundle branch block (LBBB), with an average QRS duration of 166±25ms. Ischemic aetiology of heart failure was found in 131 (33%) patients. Before CRT, ApRock and SF were present in 254 (64%) and 244 (61%) patients, respectively. ApRock and SF alone predicted CRT response with an area under the curve (AUC) of 0.79 (95% CI: 0.74–0.84) and 0.78 (95% CI: 0.73–0.83) (Figure A), while the echocardiographic Reader Interpretation had an AUC of 0.85 (95% CI: 0.81–0.89), with a sensitivity of 89% and a specificity of 82% for the prediction of CRT response (Figure B) (p<0.0001 vs. ApRock and SF alone). A total of 92 patients had a QRS duration of 120–150ms, and 48 of them responded to CRT. In these patients, the AUC of Reader Interpretation was comparable to that of the entire study cohort [0.83 (95% CI: 0.75–0.92)], as was sensitivity and specificity (90% and 79%, respectively, p=0.717 vs. the AUC of the entire cohort) (Figure C). Conclusions: A visual assessment of LV function, by means of mechanical dyssynchrony and scar, has an excellent predictive value for CRT response, and requires only apical echocardiographic images. Responders were identified equally well in the challenging subgroup of patients with a QRS duration of 120–150 ms. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): KU Leuven